Diseño de un plan de mejoramiento integral y capacitación de recursos para el centro médico María Madre de la Salud ubicado en la ciudad de Quito - Guachamin Morales, Rosario de las Mercedes (2015)
In the present work of investigation Maria Madre de la Salud carried out an offer of Plan of Integral Improvement for the Medical Center located in the south sector of the city of Quito, analyzing the current situation and the one that is waited for the future. In the first chapter the environment of the companies is described at present, in addition the problematics appears, there are established the general aim and the specific aims of the present thesis and his importance inside the organizations, the variables of the hypothesis was identified and distinguish themselves legal foundations that govern the health in the Ecuador. In the third chapter one indicates that type and method of investigation should be in use for the accomplishment of the present study, there is defined the sample and the population who will be analyzed, in the fourth chapter there is announced which is the current situation of the Medical Center Maria Madre de la Salud analyzing the internal and external environment that affects his activities. The fifth chapter shows the development of the offer of improvement to be applying, a series of strategies appeared in order to improve the functioning of the medical center and to give a value added to the service that offers. They present the conclusions to those who came near with the study and the recommendations are enunciated